2021
DOI: 10.1111/geb.13429
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization delays plant leaf senescence and extends growing season length in cold but not in warm areas of the Northern Hemisphere

Abstract: Aim: Urbanization is becoming one of the most important drivers of global environmental change as human population and economic development rapidly increase.However, the effects of urbanization on plant phenology are still poorly understood, especially for leaf senescence and growing season length across large spatial scales.We aimed to fill this knowledge gap by combining in situ observations and remote sensing phenological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…The human population density of each county through time was used as a proxy for urbanization in this study, as it is: highly correlated with the degree of urbanization (Bagan & Yamagata, 2015); often used to represent the degree of urbanization or rural-urban gradients (McDonnell & Hahs, 2008;Balk et al, 2018); and frequently used in this manner in studies of urbanization effects on phenology (Li et al, 2019(Li et al, , 2021(Li et al, , 2022Bonnet-Lebrun et al, 2020). We calculated population density based on population size and county area collected in the decadal census data from the U.S. Census Bureau (2020).…”
Section: Climate Frost Risk and Population Density Datamentioning
confidence: 99%
“…The human population density of each county through time was used as a proxy for urbanization in this study, as it is: highly correlated with the degree of urbanization (Bagan & Yamagata, 2015); often used to represent the degree of urbanization or rural-urban gradients (McDonnell & Hahs, 2008;Balk et al, 2018); and frequently used in this manner in studies of urbanization effects on phenology (Li et al, 2019(Li et al, , 2021(Li et al, , 2022Bonnet-Lebrun et al, 2020). We calculated population density based on population size and county area collected in the decadal census data from the U.S. Census Bureau (2020).…”
Section: Climate Frost Risk and Population Density Datamentioning
confidence: 99%
“…Moreover, Zani et al (2020) suggested that the increased plant productivity during the growing season is related to the earlier EOS because the amount of nonstructural carbon plants can hold is limited. The cities located in the warm and water-abundant regions generally have higher plant productivity during the growing season which might cause vegetation to hit the carbon limitation earlier than the cities located in cold regions (Li et al, 2021).…”
Section: Imprint Of Urban Warming On Vegetation Phenologymentioning
confidence: 99%
“…Los cambios incluyen un florecimiento y madurez más tempranas en los cultivos agrícolas que afectan los tiempos de siembra y cosecha 93,94,95,96,97 , estaciones alérgicas más largas e intensas (KM 14.4) 98 y una mayor actividad de las plagas 99,100 . Los cambios son más pronunciados en latitudes y elevaciones altas y en zonas urbanizadas 101,102 . Los desajustes fenológicos surgen cuando la sincronización de actividades de las especies que interactúan cambia a ritmos diferentes, como cuando la disponibilidad de alimentos deja de coincidir con las necesidades de un organismo dependiente 103,104 .…”
Section: Cambios En La Fenologíaunclassified